Structural conceptual model of forming readiness for innovative activity of future teachers in general education school - Mussabekova, Gulnar; Chakanova, Selime; Boranbayeva, Aktolkyn; Utebayeva, Aliya; Kazybaeva, Kenzhegul; Alshynbaev, Kulalbek (Opción, 2018)
Modernization of higher vocational education requires a significant rethinking of the structure and concept of the educational process in a HEI. One of the vocational training directions should be the formation of future teacher’s readiness to innovate activity, which would allow teachers to demonstrate their individual creative abilities, realize their intellectual potential, and apply the full range of knowledge, skills and experience acquired in the process of studying at hei. Creation of optimal organizational and pedagogical conditions for personal self-realization is an actual task for all levels in education, but for higher vocational education this task acquires special connotation and significance.